2017
DOI: 10.1002/ccd.27359
|View full text |Cite
|
Sign up to set email alerts
|

Second‐generation drug‐eluting stents versus drug‐coated balloons for the treatment of coronary in‐stent restenosis: A systematic review and meta‐analysis

Abstract: The two treatment strategies are equal for the treatment of ISR, while the difference in all-cause mortality might be potentially explained by baseline differences in the two groups among real-world studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…This observation was corroborated by Siontis et al (27 trials, 5923 patients) and Kokkinidis et al (10 studies, 2173 patients), which demonstrated that the use of second generation DES was the most effective strategy. 15,16 In summary, current clinical data support the use of DCB in BMS/DES ISR as an alternative to receiving a DES stent.…”
Section: Clinical Use Of Dcb In Coronary Artery Disease (Cad)mentioning
confidence: 91%
“…This observation was corroborated by Siontis et al (27 trials, 5923 patients) and Kokkinidis et al (10 studies, 2173 patients), which demonstrated that the use of second generation DES was the most effective strategy. 15,16 In summary, current clinical data support the use of DCB in BMS/DES ISR as an alternative to receiving a DES stent.…”
Section: Clinical Use Of Dcb In Coronary Artery Disease (Cad)mentioning
confidence: 91%
“…The treatment options for ISR include PCI with DESs, DCBs, or PTCA. DCBs and second-generation DESs were equally effective in treating coronary ISR, according to a new systematic review and meta-analysis [ 20 ]. Paclitaxel and rapamycin analogues have been proven successful in preventing neointimal hyperplasia and ISR.…”
Section: Evidence-based Practice Of Treating Isr Using Dcbsmentioning
confidence: 99%
“…Drug-coated balloon (DCB) angioplasty is an effective strategy for the treatment of patients with coronary ISR and showed comparable results with second-generation DES. 6,7 However, recurrent ISR after DCB angioplasty for DES ISR was also problematic with a high incidence of recurrent ISR after DCB. 8 We hypothesized that measurement of OCT-derived parameters during the procedure can predict future adverse events after DCB angioplasty for DES ISR.…”
Section: Introductionmentioning
confidence: 99%
“…Drug‐coated balloon (DCB) angioplasty is an effective strategy for the treatment of patients with coronary ISR and showed comparable results with second‐generation DES 6,7 . However, recurrent ISR after DCB angioplasty for DES ISR was also problematic with a high incidence of recurrent ISR after DCB 8 .…”
Section: Introductionmentioning
confidence: 99%